MULTIPLE EYELID LUMPS IN INFANT WITH DYSLIPIDEMIA IN RESOURCE-LIMITED SETTING ANAMBAS ARCHIPELAGO DISTRICT - Santi Febrianti (Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung, 2023)
Objective: Our aim was to present a case of recurrent multiple eyelid lumps in infant withdyslipidemia in limited resources area.